Housing Subsidies for Refugees: Experimental Evidence on Life Outcomes and Social Integration in Jordan - Abdulrazzak Tamim; Emma Smith; I. Bailey Palmer; Edward Miguel; Samuel Leone; Sandra V. Rozo; Sarah Stillman (Institute of Labor Economics (IZA), 2025)
Refugees require assistance for basic needs like housing but local host communities may feel excluded from that assistance, potentially affecting community relations. This study experimentally evaluates the effect of a housing assistance program for Syrian refugees in Jordan on both the recipients and their neighbors. The program offered full rental subsidies and landlord incentives for housing improvements, but saw only moderate uptake, in part due to landlord reluctance. The program improved short-run housing quality and lowered housing expenditures, but did not yield sustained economic benefits, partly due to redistribution of aid. The program unexpectedly led to a deterioration in child socio-emotional well-being, and also strained relations between Jordanian neighbors and refugees. In all, housing subsidies had limited measurable benefits for refugee well-being while worsening social cohesion, highlighting the possible need for alternative forms of aid.
Keywords: D22; J61; O17; 330; refugees; housing; forced migration; social integration